Analisisi perbedaan abnormal return dan trading volume terhadap pergantian menteri keuangan activity: Studi peristiwa pada saham perbankan dan energi - Sulistio Murti Mulyono; Tita Nurvita (Nur Science Institute, 2026)
Political events, particularly those related to changes in strategic economic positions, often attract investor attention due to their potential to influence economic stability and the direction of a country’s policy. The replacement of the Minister of Finance, as the primary authority in fiscal policy, can trigger market reactions reflected in stock price movements and trading activity. Previous studies have shown that political events and government policies can elicit significant market responses, including abnormal returns and changes in trading volume. In this context, this study analyzes the reaction of the Indonesian capital market to the announcement of the replacement of the Minister of Finance on September 8, 2025, focusing on stocks in the banking and energy sectors. This study employs a quantitative approach using an event study method with an observation window of 31 trading days, consisting of 15 days before, 1 day during, and 15 days after the event, using daily stock prices and trading volume data. The analysis compares conditions before and after the event using nonparametric statistical methods. The results indicate that there is no significant difference in abnormal returns between the two sectors; however, the banking sector shows a significant increase in trading volume. These findings suggest that the market responds more to political events through changes in trading activity rather than abnormal returns.